Strategies for the screening of antibiotic residues in eggs: comparison of the validation of the classical microbiological method with an immunobiosensor method. Issue 9 (2nd September 2017) - Gaudin, Valérie; Rault, Annie; Hedou, Celine; Soumet, Christophe; Verdon, Eric
ABSTRACT: Efficient screening methods are needed to control antibiotic residues in eggs. A microbiological kit (Explorer® 2.0 test (Zeu Inmunotech, Spain)) and an immunobiosensor kit (Microarray II (AM® II) on Evidence Investigator™ system (Randox, UK)) have been evaluated and validated for screening of antibiotic residues in eggs, according to the European decision EC/2002/657 and to the European guideline for the validation of screening methods. The e-reader™ system, a new automatic incubator/reading system, was coupled to the Explorer 2.0 test. The AM II kit can detect residues of six different families of antibiotics in different matrices including eggs. For both tests, a different liquid/liquid extraction of eggs had to be developed. Specificities of the Explorer 2.0 and AM II kit were equal to 8% and 0% respectively. The detection capabilities were determined for 19 antibiotics, with representatives from different families, for Explorer 2.0 and 12 antibiotics for the AM II kit. For the nine antibiotics having a maximum residue limit (MRL) in eggs, the detection capabilities CCβ of Explorer 2.0 were below the MRL for four antibiotics, equal to the MRL for two antibiotics and between 1 and 1.5 MRLs for the three remaining antibiotics (tetracyclines). For the antibiotics from other families, the detection capabilities were low for beta-lactams and sulfonamides and satisfactory for dihydrostreptomycin (DHS) and fluoroquinolones, which are usually difficult to detect with microbiological tests. The CCβ values of the AM II kit were much lower than the respective MRLs for three detected antibiotics (tetracycline, oxytetracycline, tylosin). Concerning the nine other antibiotics, the detection capabilities determined were low. The highest CCβ was obtained for streptomycin (100 µg kg –1 ).